The change trend in physiological traits of 110 citrus accessions in response to cold stress (Bangladesh Journal of Botany, 2020)
In order to investigate the change process of some physiological indices in response to four temperature levels (3, 0, ‒3 and ‒6°C), 110 Citrus accessions consisting of 76 unknown natural biotypes and 34 known genotypes were studied using the split-plot design with three replications. Two genotypes Poncirus and Mexican lime (as cold tolerant and cold susceptible, respectively) were used as control genotypes. Electrolyte leakage, leaf water soaking, and lipid peroxidation had increasing trends with the decrease of temperature. On the other hand, for tolerance criteria (antioxidant capacity, proline content, total carbohydrates, and enzymatic activities) sigmoidal trends were recorded. For electrolyte leakage and leaf water soaking, Poncirus, Satsuma mandarin, and the unknown biotype G8 had the smallest range of mean variation at four stress temperatures. Also, for lipid peroxidation, Siavaraz 1, Satsuma mandarin, and sour orange had the lowest range of change. Proline content evaluation showed that Satsuma mandarin and two natural biotypes- Moallemkoh and Siavaraz 2-experienced the highest changes in proline accumulation.